Optimization of Sustainable Copper Leaching Using Glycine and Oxidizing Agents in an Alkaline Medium - Jesús I. Martínez; Aislinn M. Teja; Martín Reyes; Norman Toro; Gabriel Cisneros; Uriel M. Flores; Miguel Pérez Labra; Gustavo Urbano; Julio C. Juarez (Metals)
The increasing global demand for copper has driven the search for more efficient and sustainable extraction methods, particularly due to the environmental concerns associated with conventional processes. This study investigated the leaching of copper minerals MC (Cu2O) and malachite (Cu2CO3(OH)2) using glycine as an organic ligand in an alkaline medium, and evaluated the efficiency of hydrogen peroxide (H2O2) and ozone (O3) as oxidizing agents. Chemical and mineralogical characterization using XRD, XRF, ICP, and SEM confirmed the predominance of MC and malachite, along with secondary phases such as hematite and calcite. Leaching experiments were carried out by varying glycine and oxidant concentrations at pH 10, with a reaction time of 240 min, agitation at 800 min−1, a solution volume of 300 mL, and a mineral sample concentration of 0.33 g·L−1. The results showed that O3 exhibited low efficiency due to its limited solubility, whereas H2O2 achieved dissolution rates of 69.7% for MC in 150 min and 96.3% for MMin just 60 min. The glycine-H2O2 system optimized reaction time by 84% compared to conventional methods, emerging as a sustainable alternative due to the low toxicity and biodegradability of glycine.